2011
DOI: 10.1002/pat.1666
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated carbon nanotubes/sulfonated poly(ether sulfone ether ketone ketone) composites for polymer electrolyte membranes

Abstract: A series of composite membranes consisting of sulfonated carbon nanotubes (sCNTs) and sulfonated poly(ether sulfone ether ketone ketone) were successfully fabricated via the solution casting method. The chemical structure, as well as the long‐term stability of the sCNTs in different solvents, was investigated by Fourier transform infrared (FTIR) analysis and solubility experiment, respectively. The morphology, tensile strength, proton conductivity, and methanol permeability of the composite membranes were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…It is observed that tensile strength is not much affected by the addition of 0.25 and 0.5 wt.% Sfu to SPEEK matrix in relation to SPEEK. Interestingly at higher loading of Sfu (1 wt.%) slight increase in tensile strength is observed may be attributed to the interfacial hydrogen bonding between Sfu and the host matrix [44], and the reduction in elongation may be due to the increased rigidity of the membranes in the presence of Sfu additive affecting the chain flexibility of SPEEK. It is important to note from Table 2 that variation in tensile strength for the membranes is not prominent in water sorbed environment.…”
Section: Physico-chemical Characterization For the Membranesmentioning
confidence: 92%
See 3 more Smart Citations
“…It is observed that tensile strength is not much affected by the addition of 0.25 and 0.5 wt.% Sfu to SPEEK matrix in relation to SPEEK. Interestingly at higher loading of Sfu (1 wt.%) slight increase in tensile strength is observed may be attributed to the interfacial hydrogen bonding between Sfu and the host matrix [44], and the reduction in elongation may be due to the increased rigidity of the membranes in the presence of Sfu additive affecting the chain flexibility of SPEEK. It is important to note from Table 2 that variation in tensile strength for the membranes is not prominent in water sorbed environment.…”
Section: Physico-chemical Characterization For the Membranesmentioning
confidence: 92%
“…Whereas for sulfonated fullerene, symmetric and asymmetric stretching vibrations of O=S=O from sulfonic acid (-SO 3 H) group are observed between 1090 and 1392 cm -1 respectively. The bands at 1630 cm -1 is due to C=C stretching and 1740 cm -1 are attributed to the presence of carbonyl group of -COOH [43] and in the lower region, C-S stretching band is observed at 710 cm -1 [44].…”
Section: Ft-ir 1 H-nmr and Xps Analysis Of Sulfonated Fullerene (Sfu)mentioning
confidence: 96%
See 2 more Smart Citations
“…Although most applications of carbon nanotubes in fuel cells are related to their use as electrodes and catalyst support (which is outside the scope of this review), they also play a role in improving the membrane structure. Zhou et al [184] developed composite membranes consisting of sulfonated carbon nanotubes (sCNTs) and sulfonated poly(ether sulfone ether ketone ketone) for use in fuel cells. They found that the addition of either PETA PEO Ketoprofen pristine carbon nanotubes or modified carbon nanotubes significantly enhances the tensile strength of the membrane; the proton conductivity increased while the methanol permeability decreased as the sCNTs content increased.…”
Section: Fuel Cellsmentioning
confidence: 99%